Re-examining the moderating role of ICT in the nexus between financial development and banking efficiency: evidence from Africa - Emmanuel Issifu Fuseini; Muazu Ibrahim; Ibrahim Osman Adam; Xuan Vinh Vo (Cogent Economics & Finance, 2024)
Studies on the tripartite nexuses among information and communication technology (ICT), financial development (FD), and banking sector efficiency have largely produced mixed findings. More importantly, how countries' levels of ICT advancement moderate FD-banks efficiency interlinkages need to be re-assessed. By utilizing data from 48 African countries covering 2004 to 2021 in assessing the tripartite interlinkages, the empirical findings based on the system Generalized Method of Moments (GMM) show that ICT goods imports significantly impact the banking sector positively in enhancing financial access to allocate finance efficiently: Individuals using the internet enhances the banking sector's efficiency. Fixed telephone subscriptions, Mobile cellular subscriptions, and secured internet servers impact banking sector efficiency insignificantly. Financial formalization and informalization significantly impact banking sector efficiency positively, except in the case of ICT goods imports being added to the equation. On the moderating role of the ICT proxies, our finding showed that how ICT moderates the impact of FD on banking sector efficiency is conditioned on both the proxy of ICT and FD. Further findings show an inverted U-shaped relationship between individuals using the internet, ICT goods imports, and the banking sector efficiency nexus. The study discusses the implications for policy and makes key recommendations to improve ICT infrastructure and FD. The role of financial development in banking sector efficiency cannot be overemphasized. At the same time, how information and communication technology (ICT) mediate the link between financial development and banking sector efficiency is gaining traction. This study therefore examines these tripartite relationships. Based on the findings, it is uncovered that the integration of ICT into the banking industry can provide efficiency gains that are not directly related to financial sector formalization or informalization.
Keywords: 330; ICT; efficiency; financialdevelopment; GMM